Pengaruh Plant Catalyst dan POC Kotoran Kambing Terhadap Pertumbuhan dan Produksi Bawang Kucai (Allium Chinense G. Don): The Effect of Catalyst Plant and Goat Manure POC on The Growth and Production of Green Onions (Allium chinense G. Don) - rustam baraq noor; Zainudin; Hermansyah (Universitas Widya Gama Mahakam, 2022)
ABSTRACT This reseach is aim Response of Plant Catalyst and Goat Dung Liquid Organic Fertilizer on the Growth and Production of Allium chinense G. Don. In Implementation for four months from Mei to Augurt 2021. Reseach sites on Bung Tomo street Gang Surya Indah RT 23 Sungai Keledang Village, Samarinda Seberang District, Samarinda City. East Kalimantan Province The research design used a randomized completely block design (RCBD) repeate three times. plant catalyst four level and growing medium four. The fist factor is Plant Catalyst 2006 (P) : P0 = without Plant Catalyst 2006 (Control), P1 = 0.5 g Plant Catalyst 2006 per liter of water, P2 = 1 g Plant Catalyst 2006 per liter of water, P3 = 1,5 g Plant Catalyst 2006 per liter of water and the second factor is the Goat Dung Liquid Organic Fertilizer (K), namely: Goat Dung Liquid Organic Fertilizer K0 =o ml/water , K1 = 5 ml/ L water (3:1), K2 = 10 ml / L water, K3 = 15 ml/ L water The results showed that the application of Plant Catalyst fertilizer (P) had no significant effect on all observation variables, the application of POC goat manure (K) had a significant effect on the observed variables for the number of bulbs and bulb weight of Allium tuberosum bulbs with K3 treatment (15 ml / liter of water) which gave the results the best. The interaction of the application of Plant Catalyst fertilizer and POC manure had a significant effect on the observed variables on the number of Allium chinense G. Don bulbs, but had no significant effect on the variables observed for the number of leaves, bulb volume and weight of Allium tuberosum bulbs, P2K1 treatment (1 gram/ltr of water and 5 ml/ltr of water). ) which gives the best results The results showed of plant Catalyst treatment non signifint and growing media treatment higly signifint. effect on the number of leaves 28 DAP, 42 DAP, 56 DAP, 70 DAP, number of tubers 70 DAP, root length 70 DAP, and tuber wet weight 70 DAP. The best treatment is growing medium that is top soil and goad manure (3:1). Recommendation to use Goat Dung Liquid Organic Fertilizer 15 ml / liter of water for the cultivation of Allium chinense G. Don. Key word : plant catalyst, Goat Dung Liquid Organic Fertilizer, Allium chinense G. Don.